Weaving Indigenous and Western knowledge systems across a continuum of knowledge and decision-making spaces - Natalie C Ban; Hannah V Watkins; Robyn E Forrest; Alejandro Frid; Carrie A Holt; Sierra J Hall; Christina N Service; Luisa Ramirez; Daniel L Curtis; Kyle L Wilson; Lawrence Ignace; Andrea J Reid; et al. (Current Opinion in Environmental Sustainability, 2026)

Body Condition as a Shared Response to Environment in a Commercially Important Demersal Fish Assemblage - Philina A. English; Sean C. Anderson; Robyn E. Forrest (Fish and Fisheries, 2026)
Measures of an organism's weight at a given length are often considered reliable indicators of energy reserves or ‘condition’, which can be related to fecundity and risk of mortality. Understanding the impact of environmental change on fish condition may therefore inform sustainable management of human activities in marine ecosystems. We investigated how changes in Canadian Pacific waters may be influencing the average condition of 35 commercially, culturally, and/or ecologically important demersal fish species. Because the condition of mature male and female, and immature individuals differs in its implications for population dynamics, ecological drivers, and measurement variability, we analysed these three maturity groups separately. We estimated density distributions, calculated Le Cren's relative body condition deviations, modelled spatiotemporal change in these deviations, and generated density‐weighted annual indices of body condition. We used Bayesian Dynamic Factor Analysis to identify common trends across species and tested for correlations with environmental variables. For most species, warmer sea surface temperature and lagged North Pacific Gyre Oscillation appeared neutrally or positively correlated with condition. Only the immature condition was also strongly correlated with primary production, but this effect was equally likely to be negative (e.g., Pacific Spiny Dogfish, Lingcod, and Sablefish) as positive (e.g., Quillback Rockfish, Southern Rock Sole, and Spotted Ratfish). Our approach propagates uncertainty from condition estimation through to environmental correlations to provide both ecosystem‐level and species‐specific inference. Robust estimates of relationships between condition and environmental variables can inform ecosystem approaches to fisheries management, including short‐term forecasts of weight‐at‐age or recruitment.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Quota use in mixed‐stock fisheries - William A. Karp; Michael C. Melnychuk; Robyn E. Forrest; Lorne Richard Little; Kristin McQuaw; Chad Demarest; Ray Hilborn; Nicole Baker; Brian Mose; Bruce Turris; Ernesto Penas Lado (Fish and Fisheries, 2024)
Although most fisheries assessment and management focuses on the status of individual stocks, and regulations are commonly established as single‐species total allowable catch limits (TACs), much of the catch from global fisheries comes from mixed‐stock fisheries where species cannot be harvested separately. We show that in some fisheries where TAC and catch of demersal fish stocks are tracked, the average fraction of TAC harvested ranges from 21% to 68% overall and is declining. This is, in part, related to efforts to protect all species from overfishing, leading to ‘choke species’, which limit fishing pressure on other target species. While some choke species arise from a mix of low and high‐productivity species, others result from allocation processes, which can be aggravated by shifting distributions due to climate change. Underutilization of TACs can also result from market limitations, low value of individual species, undercapacity or management measures. Proposed methods for increasing long‐term yield require species to be managed in stock groups, or allowing the abundance of some stocks to fall below target reference points. We suggest that the observed low and declining aggregate harvests are due, primarily, to the focus on single‐stock sustainability measures, rather than performance of the fisheries in relation to potential overall yield. While there is a growing consensus that single‐species management should be replaced by an ecosystem‐based approach, this will require clear legislative directives regarding management of the trade‐offs involved. Time series considered in this analysis do not extend beyond 2019.

Re‐imagining the precautionary approach to make collaborative fisheries management inclusive of Indigenous Knowledge Systems - Alejandro Frid; Kyle L. Wilson; Jennifer Walkus; Robyn E. Forrest; Mike Reid (Fish and Fisheries, 2023)
Fisheries science uses quantitative methods to inform management decisions that reflect cultural preferences which, in turn, indirectly influence the states of ecosystems. To date, it has largely supported Eurocentric preferences for the commodification of marine organisms under the tenets of maximum sustainable yield, whereby abundances are intentionally maintained far below their historical baselines despite broader socio‐ecological trade‐offs. In contrast, Indigenous Knowledge Systems (IKS) adhere to the principle of “take only what you need and leave lots for the ecosystem,” implementing lower fishery removals to support socio‐ecological resilience. Despite the power imbalance favouring Eurocentric preferences in decision‐making, fisheries scientists increasingly recognize that the pairing of IKS and Western science, or Two‐Eyed Seeing, would lead to more holistic management goals. For recognition to transcend tokenism, meaningful collaborations and co‐governance structures underlying knowledge co‐production must carry through to legislated policy changes. Using recent co‐governance developments for fisheries management and spatial protections involving federal, provincial and Indigenous governments in Pacific Canada, we illustrate how the precautionary approach, including reference points and harvest control rules broadly applied in international fisheries, could be revised to make collaborative fisheries management compatible with IKS and improve biodiversity and fisheries protections. Our recommendations may create socio‐economic trade‐offs at different timescales for commercial fishers. Pre‐empting that challenge, we discuss IKS‐compatible economic approaches for addressing shorter term costs arising from reduced exploitation rates. Although our case study derives from Pacific Canada, the insights provided here are broadly applicable elsewhere in the world.

Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters - Philina A. English; Eric J. Ward; Christopher N. Rooper; Robyn E. Forrest; Luke A. Rogers; Karen L. Hunter; Andrew M. Edwards; Brendan M. Connors; Sean C. Anderson (Fish and Fisheries, 2022)
Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.

The interim management procedure approach for assessed stocks: Responsive management advice and lower assessment frequency - Quang C. Huynh; Adrian R. Hordyk; Robyn E. Forrest; Clay E. Porch; Sean C. Anderson; Thomas R. Carruthers (Fish and Fisheries, 2020)
Stock assessments are often used to provide management advice, such as a total allowable catch (TAC), to fishery managers. Many stocks are not assessed annually, and the TAC from the previous assessment is often maintained in years between assessments. We developed two interim management procedures (MPs) that update the estimate of current vulnerable biomass from a surveyed index of abundance to adjust the TAC from a previous assessment. These MPs differ in how they handle uncertainty in observed indices. Using closed‐loop simulation, we evaluated the two interim MPs (with 10‐ and 5‐year assessment intervals) against several “status quo” approaches: (1) an annual assessment, and (2) a stock assessment every 5 or 10 years with (a) fixed TACs or (b) projections between assessments. We evaluated performance across three life‐history types and six operating model scenarios. The interim MPs performed similarly to annual assessments in terms of trends in biomass and yield, regardless of the assessment interval of the interim MPs. The interim MPs often produced more yield than the Fixed TAC MP with 10‐year assessment intervals, for example, in depleted scenarios. The Fixed TAC MP performed more similarly to interim MPs when the assessment interval for the Fixed TAC MP was decreased to five years. The interim MPs can also perform well when circumstances arise that are not accounted for in the Projection MP. Our results show that interim MPs should be considered for infrequently assessed stocks or rebuilding stocks, and highlight potential cost savings of interim MPs over annual assessments.